What Factors Influence Union and Refracture of Congenital Pseudarthrosis of the Tibia? A Multicenter Long-term Study. Issue 6 (July 2018) - Shah, Hitesh; Joseph, Benjamin; Nair, Binu V.S.; Kotian, Devaki B.; Choi, In Ho; Richards, Benjamin Stephens; Johnston, Charles; Madhuri, Vrisha; Dobbs, Matthew B.; Dahl, Mark
Abstract : Objective: To identify factors influencing union of congenital pseudarthrosis of the tibia (CPT), refractures, and integrity of the tibia at maturity. Methods: Data of 119 children operated for Crawford-type IV CPT and followed-up till skeletal maturity were analyzed. Logistic regression and recursive partitioning analyses were used to test associations between several variables and the outcome. Results: Primary union occurred in 86% of children. At maturity, 69% remained soundly united. The odds ratio for failure of primary union was 3.89 (95% confidence interval, 1.05-14.40; P =0.042) when bone morphogenetic protein was used, and children who had a combination of the Ilizarov technique and intramedullary nailing were at risk for unsound union at maturity (odds ratio, 6.19; 95% confidence interval, 1.24-30.83; P =0.026). No other association reached statistical significance. On recursive partitioning, use of the Ilizarov technique, transfixing the ankle and subtalar joints, use of cortical graft and not operating on the fibula were associated with a better outcome; use of bone morphogenetic protein and combining intramedullary nailing with the Ilizarov technique were associated with poor results. Conclusions: A larger sample is needed to confirm which factors truly influence the outcome of CPT. This may be feasible if data are collected prospectively through a multicenter registry. Abstract : Supplemental Digital Content is available in the text.